2005
DOI: 10.1243/095765005x5990
|View full text |Cite
|
Sign up to set email alerts
|

CO2 and H2O diluted oxy-fuel combustion for zero-emission power

Abstract: Concerns about climate change have encouraged significant interest in concepts for zero-emission power generation systems. These systems are intended to produce power without releasing CO2 into the atmosphere. One method to achieve this goal is to produce hydrogen from the gasification of fossil or biomass fuels. Using various membrane and reforming technologies, the carbon in the parent fuel can be shifted to CO2 and removed from the fuel stream, followed by direct CO2 sequestration. The hydrogen fuel can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 10 publications
1
41
0
3
Order By: Relevance
“…Richards et al (2005) calculate the equilibrium concentration of CO in the CES cycle combustion products to be 5-7 times lower than for CO 2 moderated combustion. At 1650 K, 10 bar and ϕ = 0.98 the equilibrium concentration of 12 ppmv is reached in 4 ms. For a CO 2 recycle, 200 ppmv in 20 ms are reported as in Section 4.…”
Section: Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Richards et al (2005) calculate the equilibrium concentration of CO in the CES cycle combustion products to be 5-7 times lower than for CO 2 moderated combustion. At 1650 K, 10 bar and ϕ = 0.98 the equilibrium concentration of 12 ppmv is reached in 4 ms. For a CO 2 recycle, 200 ppmv in 20 ms are reported as in Section 4.…”
Section: Emissionsmentioning
confidence: 99%
“…Though low emissions of CO and O 2 are favoured at low flame temperatures, a kinetic approach revealed that the equilibrium concentrations are not reached at a fixed residence time of 40 ms. Higher pressure reduces the equilibrium concentration due to Le Chatelier's principle and leads to faster reaction rates. Richards et al (2005) investigate the CO emissions of an oxyfuel gas turbine combustor with a combined network of perfectly stirred reactor and a plug flow reactor (PSR/PFR) model. For a recycle stream consisting mainly of CO 2 at 10 bar and a flame temperature of 1650 K the equilibrium concentration of 200 ppmv is reached in 20 ms for ϕ = 0.98 .…”
Section: Emissionsmentioning
confidence: 99%
“…Therefore, it is essential to study the fundamental burning properties of syngas over a wide range of composition under representative operating conditions of advanced gas turbines. With the development of carbon capture and storage (CCS) technique [2], burning syngas with large amount of CO 2 becomes an effective way to reduce NO X emission (e.g. in oxy-fuel combustion).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that AramcoMech 1.3 does not contain a model for formation of nitrogen oxides (NOx). However this is not expected to be a major problem when dealing with oxy-fuel combustion, since a number of studies have found NOx formation to be negligible for realistic O 2 purities [16][17][18].…”
Section: Mechanism For Oxy-fuel Combustion Of Chmentioning
confidence: 99%